Evaluation of radon adsorption efficiency values in xenon with activated carbon fibers. (13th November 2020) - Nakano, Y; Ichimura, K; Ito, H; Okada, T; Sekiya, H; Takeuchi, Y; Tasaka, S; Yamashita, M
Abstract: The radioactive noble gas radon-222 (^222Rn ) produced in the uranium series is a crucial background source in many underground experiments. We have estimated the adsorption property of Rn with activated carbon fibers (ACFs) in air, argon, and xenon gas. We evaluated six ACFs, named A-7, A-10, A-15, A-20, A-25, and S-25, provided by Unitika Ltd. We measured the intrinsic radioactivity of these ACF samples, and found A-20's radioactivity of the uranium series to be <5.5 mBq/kg with 90% confidence level. In air and Ar gas, we found that ACF A-15 has an adsorption efficiency of 1/10000 reduction at maximum before saturation of Rn adsorption, and more than 97% adsorption efficiency after the saturation. In Xe gas, we found that ACF A-20 has the best Rn adsorption ability among the tested ACFs. We also found that S-25, A-25, and A-15 have similar Rn adsorption performance.